Management of Working Capital in IFFCO and KRIBHCO - A Comparative Study - Singh, Swaran; Bansal, S. K. (Indian Journal of Finance, 2010)
The Indian Fertiliser Industry entered into the hundredth year of its existence in the year 2006. The industry had a very humble beginning in 1906, when the manufacturing unit of Single Super Phosphate (SSP) was set up in Ranipet near Chennai with annual capacity of 600 MT. The Fertiliser&Chemicals Travancore of India Ltd. (FACT) at Cochin in Kerala and the Fertiliser Corporation of India (FCI) in Sindri in Bihar were the first large sized fertiliser plants set up in forties and fifties with a view to establish an industrial base to achieve self-sufficiency in food grains. Subsequently, green revolution in the late sixties gave an impetus to the growth of fertiliser industry in India. In seventies and eighties, a significant addition to the fertiliser production capacity was witnessed. There has been spectacular growth in the production capacity and production of fertilisers, particularly during eighties and early nineties to meet the rising demand of fertilisers. The Indian fertiliser industry is one of the best in the world in terms of capacity utilisation.